Analysis of the Influence of Halal Products and Brand Image on Food Product Purchase Decisions in Makassar - Qasabandiyah, Muhammad Kholidinna; Farida, Umi (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2024)
The increasing awareness of halal products among consumers has significantly influenced purchasing decisions, especially in the food industry. This study aims to analyze the influence of halal product attributes and brand image on consumer purchase decisions in Makassar. Using a quantitative research approach, data were collected through surveys distributed to consumers who frequently purchase food products. The analysis was conducted using multiple regression techniques to determine the relationship between the variables. The findings indicate that halal certification, product ingredients, and compliance with Islamic law significantly impact consumer trust and preferences. Additionally, brand image plays a crucial role in shaping consumer perceptions, influencing their likelihood of purchasing food products. The study highlights that consumers in Makassar prioritize halal aspects in their purchasing decisions, alongside brand reputation and product quality. These results provide valuable insights for food businesses to enhance their marketing strategies by emphasizing halal certification and strengthening their brand image. Future research could explore additional factors such as pricing and consumer loyalty to gain a more comprehensive understanding of purchasing behavior..